Getting Great Sounds: The Microphone Book - Lubin, Tom (Rowman & Littlefield Publishers, 2022)
Getting Great Sounds: The Microphone Book imparts microphone tips and tricks of the pros to make them available to any sound engineer or home studio enthusiast. It explains aspects of all kinds of microphones, how they work, and how to use them in session recording. A well-known recording engineer with decades of industry experience, Tom Lubin presents technical information in a friendly, straightforward, and easy-to-grasp way, based on real-life experiences. This third edition includes a review of key practices at the end of chapters and a new section that provides an overview of microphone manufacturers you may not have heard of. There are now over one hundred and fifty companies making microphones for studio applications of one form or another, and most are small companies owned by people who are passionate about good sound. These companies feature high quality microphones, and many use classic designs with more affordable prices. How to choose and use microphones was once a skill passed down from senior sound engineers to their assistants as they would listen and learn by observation. Today, few large studios have assistant engineers, and an overwhelming number of studios are operated by their owners who are often self-taught and lack the benefit of the big-studio tutelage. This book is your guide to understanding the ins and outs of microphones and music studio production.